2022
DOI: 10.1002/acr.24455
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Low‐Density Lipoprotein, High‐Density Lipoprotein, and Total Cholesterol With Development of Knee Osteoarthritis

Abstract: Objective Studies suggest an association between elevated total serum cholesterol, particularly low‐density lipoprotein (LDL), and osteoarthritis (OA). The present study was undertaken to evaluate the association between total cholesterol, LDL, and high‐density lipoprotein (HDL) and risk of knee OA. Methods We studied participants from the Multicenter Osteoarthritis study (MOST) cohort at risk of developing knee OA. From baseline through 7 years, repeated knee radiographs and magnetic resonance images (MRIs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…was even more direct in finding that pravastatin significantly reduced IL‐1β induced MMP‐1 and MPP‐13 expression as well as intracellular cholesterol expression in human chondrocytes of OA patients. However, numerous studies have reported that there is no direct link between OA and cholesterol metabolism 12,56 . Our research identified an obvious and significant increase in serum and synovial fluid TC levels of patients with OA among 74 patients and synovial fluid TC levels correlated better with OA severity compared to serum TC levels.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…was even more direct in finding that pravastatin significantly reduced IL‐1β induced MMP‐1 and MPP‐13 expression as well as intracellular cholesterol expression in human chondrocytes of OA patients. However, numerous studies have reported that there is no direct link between OA and cholesterol metabolism 12,56 . Our research identified an obvious and significant increase in serum and synovial fluid TC levels of patients with OA among 74 patients and synovial fluid TC levels correlated better with OA severity compared to serum TC levels.…”
Section: Discussionmentioning
confidence: 49%
“…However, numerous studies have reported that there is no direct link between OA and cholesterol metabolism. 12,56 Our research identified an obvious and significant increase in serum and synovial fluid TC levels of patients with OA among 74 patients and synovial fluid TC levels correlated better with OA severity compared to serum TC levels. Our in vitro experiments revealed increased cholesterol uptake in OA cartilage, and the increased cholesterol further exacerbated the progression of OA.…”
Section: Discussionmentioning
confidence: 68%
“…One previous study reported no significant difference in serum APOA1 levels between OA patients and healthy controls [ 37 ]. Schwager et al also found no significant association between HDL and OA based on the Multicenter Osteoarthritis Study (MOST) cohort [ 12 ]. Genetic causality between HDL and TG with OA was also absent in a UKBB based MR study [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…An association between serum cholesterol levels and OA was subsequently reported with hand OA in women [ 9 ] and with knee OA [ 10 ]. Nevertheless, many studies have presented contradictory results [ 11 , 12 ], including the lack of a significant correlation between serum cholesterol and radiographic knee OA in an early study from Gothenburg [ 11 ], and no association between plasma low density cholesterol (LDL) or low HDL and the radiographic or symptomatic OA risks in the Multicenter Osteoarthritis Study (MOST) cohort [ 12 ]. By contrast, two recent large meta-analyses studies have shown a strong relationship between dyslipidemia and OA [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between dyslipidemia and OA is a controversial issue [ 44 , 45 ]. However, various studies revealed a significant relationship between lipotoxicity resulting from dyslipidemia and OA [ 41 , 43 , 46 ].…”
Section: Obesity-oa Interplay Beyond Mechanical Loadingmentioning
confidence: 99%